Analysis of the Implementation of the Social Environment Based Inquiry Model in Social Sciences Subjects at UPT SPF SD Inpres Baraya 1 Makassar City - Aswira, Aswira; Yunus, Muh; Rahman, Nawir (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to analyze the application of the social environment-based inquiry model in Social Sciences (IPS) subjects at UPT SPF SD Inpres Baraya 1. The research method used is descriptive qualitative with data collection methods, namely interviews with students who have taken part in learning using the inquiry model. based on the social environment. The results of the interviews showed that students felt more involved and enthusiastic in the learning process. They stated that this approach made social studies material easier to understand because they could see the real application of the concepts learned through observations and activities in the surrounding environment. Apart from that, the application of this inquiry model also contributes to improving students' social skills. Students reported increased confidence in speaking in front of the class, ability to work collaboratively in groups, and skills in listening and respecting the opinions of others. Frequent group discussions and collaborative assignments in this model help students develop better communication and collaboration skills. The results of this research are that the social environment-based inquiry model is effective in improving students' social skills and understanding of social studies material. The suggestions put forward include increasing teacher training, developing learning resources, collaborating with the surrounding environment, strengthening evaluation and reflection, and increasing parent participation. It is hoped that a more optimal implementation of this model can have a more significant impact on students' academic and social development